POSSIBLE THERAPEUTIC POTENTIAL OF STATIN INDEPENDENT OF LIPID-LOWERING ACTIVITY - Bajaad, Jyoti; Bedi, Onkar; Soni, Neha; Bijjem, Krishna Reddy V. (Asian Journal of Pharmaceutical Research and Development, 2013)
Since the discovery of the first statin nearly 30 years ago, this class of drugs has advanced to become the mainstay of cholesterol-lowering therapy to reduce the incidence of cardiovascular events in patients with or without coronary artery disease. Accumulating evidence clearly suggest that statin also induce non-lipid-modifiable action known as pleiotropic effect which could be responsible for this additional benefits. The most important positive pleiotropic effects of statins are antiinflammatory, antiproliferative, and antithrombotic effects. Statins are also directly involved in restoring or improving endothelial function, attenuation vascular remodeling, inhibition of vascular inflammatory response, and perhaps stabilizing atherosclerotic plaques. In particular, inhibition of Rho and its downstream target, Rho-associated protein kinase (ROCK), has emerged as the principle mechanisms underlying the pleiotropic effects of statins. Statins have antiatherosclerotic, antiinflammatory, antioxidant, immunomodulatory and antithrombotic effects. It applies equally to diseases of chronic inflammation type, as to those, where bone metabolism is disturbed. It is also documented that statins could decrease bone fracture risk; through bone formation intensification, and inhibition of bone tissue resorption. Slowing down the atherosclerosis progression is a very important effect, considering that in rheumatoid arthritis (RA) and in systemic lupus erythematosus (SLE) we are dealing with premature and rapid progression of atherosclerotic lesions.